1997
DOI: 10.1164/ajrccm.156.5.9702084
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Linkage Between Asthma/Atopy in Childhood and Chromosome 5q31-q33 in a Japanese Population

Abstract: Susceptibility to the development of asthma and other atopic diseases is known to be associated with genetic components, and several candidate genes have been reported to be linked to atopy in Caucasian populations. We conducted a study of linkage between asthma and markers on chromosomes 5q31-q33 and 11q13 in 68 Japanese families (306 members) by affected sib-pair analysis. Families for the linkage study were ascertained through asthmatic children visiting the allergy clinic. The results provide supportive ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
2
2

Year Published

2000
2000
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(107 citation statements)
references
References 26 publications
5
98
2
2
Order By: Relevance
“…Chromosome 5q31-q33 is linked to atopy and/or asthma and bronchial hyper-responsiveness. 8,[22][23][24][25][26][27][28] Thus, the weak but positive findings of linkage to 5q33 in the present study may reflect one of the loci common to asthma and SAR.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Chromosome 5q31-q33 is linked to atopy and/or asthma and bronchial hyper-responsiveness. 8,[22][23][24][25][26][27][28] Thus, the weak but positive findings of linkage to 5q33 in the present study may reflect one of the loci common to asthma and SAR.…”
Section: Discussionmentioning
confidence: 49%
“…Linkage of atopy and total serum IgE levels to chromosome 5q31-q33 and 12q24 has been reported. 8,[22][23][24][25][26][27][28][29] Weak linkage of asthma to chromosome 3p24 was also reported in the Hutterites. 6 Suggestive evidence for linkage of specific IgE against OG to 4p16.1, 11q14.3, and 16p12.3 was observed in the present study.…”
Section: Discussionmentioning
confidence: 79%
“…Among other biological activities (10), it was recently suggested on the basis of genetic linkage analyses that IL-9 might play an important role in the pathogenesis of asthma (18,19). This assumption was supported by the lung-specific expression of IL-9 in transgenic mice, which was accompanied by airway inflammation, bronchial hyper-responsiveness, and mast cell hyperplasia (20) as well as the increased expression of IL-9 and its receptor in human patients with atopic asthma (21).…”
Section: Il-9 and Il-13 Production By Activated Mast Cells Is Stronglmentioning
confidence: 99%
“…In 68 Japanese families ascertained through asthmatic children a positive linkage has also been found between asthma and atopy and gene markers in or near the IL-4 and Il-9 genes and D5S393 on chromosome 5q31-33. 18 In addition to candidate gene studies, The Collaborative Study on the Genetics of Asthma (CSGA), using a genome-wide search, also found linkage between asthma and 5q31-33 in Caucasian families 19 and also between 5q31-q33 and specific IgE responses to HDM in African-American families. 20 In contrast however two other large genome scans of Caucasian subjects have failed to find any strong evidence of linkage between 5q31-33 and any atopy or asthma phenotypes.…”
Section: Resultsmentioning
confidence: 99%